An improved P&O MPPT control algorithm for increasing power extraction efficiency of solar PV module. (October 2019) - Dinesh Kumar, D; Babu, Challa; Jyotheeswara Reddy, K; Kumar, K; Kumar, N K
Abstract: The extraction of solar energy is done by using power point tracking techniques. The solar PV cells available have low efficiency in the order of 15-20%. The extraction efficiency depends on solar insolation, cell temperature, angle of incidence and the load current. These factors resulting a non linear V-I characteristics for a PV cell. A Perturb & Observation MPPT is developed to operate the PV cell at a reference voltage corresponding to maximum power point in the characteristic curve. This algorithm is incorporated to improve the performance and thereby increasing the efficiency of PV cell. A 225W solar PV module at different cell temperatures and solar insolation is simulated in MATLAB environment. The simulated results shows the deviation of output power of solar module at maximum power point with ideal PV power is about 12% for different cell temperature and solar insolation.